FIDES QUAERENS SOCIALEM IUSTITIAM: Kritik Perspektif Gereja Katolik Atas Surat Edaran Mahkamah Agung Nomor 2 Tahun 2023 - Febriano, Yoga; Reno, Victorius (Aggiornamento, 2024)
The focus of this research is the implication of SEMA Number 2 of 2023 on mixed marriages in the Catholic Church. In this SEMA, it is stated that it is prohibited for courts to grant application for registration of marriages between people of different religions and beliefs. For the Catholic Church, this has serious implications, because the Catholic Church provides space for mixed marriages with the provisions regulated in the Code of Canon Law. The aim of this research is to provide information, especially to Catholics, regarding their marital status before ecclesiastical and civil authorities. Furthermore, it is also hoped that this research can help Catholics consider and decided on fundamental matters before getting marriage. This research uses qualitative methods through critical discourse studies. Through this research, the author found that the Church provides dispensation for its members to be able to enter into mixed marriages on the grounds that marriage is a universal human right given by God. In the legal context in Indonesia, mixed marriages are still a serious problem, giving rise to debate. Therefore, for members of the Catholic Church who wish to enter into a mixed marriage, they should pay close attention to the juridical implication that follow the marriage.